Sistem Urban Farming pada Kawasan Pemukiman dalam Upaya Menambah Pendapatan Keluarga di Kota Pontianak - Arpandi, Julian; Kurniati, Dewi; Suharyani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
In this modern era, rapid urban growth and the reduction of land due to urbanization have led to dense urban settlements and limited open land for agriculture. However, food security remains a top priority in cities, while household incomes in residential areas are limited. This research focuses on hydroponics as a solution to enhance the availability of local food hence the household spending in urban terrioty with limited land. The intention of this study is to observed the hydroponic urban farming method used, analyze on-farm and off-farm income, and assess the contribution of income from hydroponic urban farming to household income. This research utilizes a quantitative descriptive method, involving surveys and interviews with respondents.While hydroponics is known in the city of Pontianak, community participation remains low. The Nutrient Film Technique (NFT) and Deep Water Culture (DWC) systems are commonly used, each with its own advantages. However, further efforts are needed to increase community participation and ensure the sustainability of hydroponic urban farming. Income from hydroponic farming is relatively lower than non-hydroponic income, primarily because respondents' main focus is on non-agricultural employment. Hydroponic farming is conducted as a side activity with limited land in their home yards. Therefore, income from hydroponic farming is lower compared to non-hydroponic income.